2016
DOI: 10.2298/sarh1604146b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency of clomiphene citrate and letrozole in combination with metformin in moderately obese clomiphene citrate - resistant polycystic ovarian syndrome patients

Abstract: This retrospective study demonstrated the advantages of the use of letrozole over clomiphene citrate in combination with metformin in moderately obese patients with polycystic ovary syndrome who are resistant to stimulation with clomiphene citrate alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Similarly, Bjelica and fellows studied 60 moderately obese women with PCOS, treated with either clomiphene citrate-metformin 31 patients or letrozolemetformin combinations 29 patients. They found that the number of follicles that > 18 mm did not show a statistically significant difference between the two groups, which is in agreement with our results [18]. Contrariwise, AlFozan and co-workers found that the total numbers of follicles during stimulation were similar between the Letrozole and CC groups (5.5 ± 0.4 in the letrozole group, 4.8 ± 0.3 in the CC group).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Bjelica and fellows studied 60 moderately obese women with PCOS, treated with either clomiphene citrate-metformin 31 patients or letrozolemetformin combinations 29 patients. They found that the number of follicles that > 18 mm did not show a statistically significant difference between the two groups, which is in agreement with our results [18]. Contrariwise, AlFozan and co-workers found that the total numbers of follicles during stimulation were similar between the Letrozole and CC groups (5.5 ± 0.4 in the letrozole group, 4.8 ± 0.3 in the CC group).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, HRT has strict indications and contraindications, which require that patients return regularly hospital so that the risks of treatment can be evaluated, and this limits its use in clinical applications (Panel, 2017). For ovulation induction, the first-line drug in clinical practices is clomiphene citrate, which causes thin endometrium as well as high ovulation and low pregnancy occurrence (Bjelica et al, 2016;Reed et al, 2018). Letrozole, an aromatase inhibitor traditionally used for breast cancer, is also used for ovulation induction.…”
Section: Introductionmentioning
confidence: 99%
“…Another study done among moderately obese women showed significantly higher pregnancy rate among the letrozole-metformin group (20.6%) than the CC-metformin group (9.6%) [20]. These higher pregnancy rates among letrozole group in most of the studies might be because letrozole was used among those PCOS women who were resistant to CC.…”
Section: Discussionmentioning
confidence: 96%
“…Use of metformin is associated with more controlled and orderly ovulation and fertility induction [8,11,17]. Many studies have been conducted to identify the combined effect of metformin with CC or letrozole [8,11,15,[18][19][20][21][22][23]. Improved results have been observed with combined medication than using CC or letrozole alone.…”
Section: Introductionmentioning
confidence: 99%